Peran Informasi Akuntansi Manajemen Terhadap Keberhasilan Strategi Green Business Pada Usaha Budidaya Jamur Tiram Team 10 Jakarta Barat - Indah Nur Cahyani; Dyah Ayu Wulandari; Irene Ismail; Aulia Nur Kusuma (Journal of Agribusiness, Social and Economic, 2026)
This study discusses the role of management accounting information in green business strategies at Team 10 Oyster Mushroom Cultivation in West Jakarta. The research method used was a qualitative method through interviews, observations, and literature studies. The results show that management accounting information helps improve operational efficiency, control costs, and support the implementation of environmentally friendly practices. The application of management accounting in line with the concept of green business encourages the creation of sustainable and competitive businesses.